If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + 10(12 + -1x) = 5(3x + -7) 25 + (12 * 10 + -1x * 10) = 5(3x + -7) 25 + (120 + -10x) = 5(3x + -7) Combine like terms: 25 + 120 = 145 145 + -10x = 5(3x + -7) Reorder the terms: 145 + -10x = 5(-7 + 3x) 145 + -10x = (-7 * 5 + 3x * 5) 145 + -10x = (-35 + 15x) Solving 145 + -10x = -35 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 145 + -10x + -15x = -35 + 15x + -15x Combine like terms: -10x + -15x = -25x 145 + -25x = -35 + 15x + -15x Combine like terms: 15x + -15x = 0 145 + -25x = -35 + 0 145 + -25x = -35 Add '-145' to each side of the equation. 145 + -145 + -25x = -35 + -145 Combine like terms: 145 + -145 = 0 0 + -25x = -35 + -145 -25x = -35 + -145 Combine like terms: -35 + -145 = -180 -25x = -180 Divide each side by '-25'. x = 7.2 Simplifying x = 7.2
| 41x-12(x-4)= | | 20=20*log(x) | | 7x+17x-7=6(4x+10) | | x^2+5x-2x=12-8 | | 0.25x+25=0.50x+15 | | -3.268=0.3k-0.7 | | 0.5x+3=0.75-7.75 | | -5(6k+9)=-27+7k | | 20=20log(x) | | 0.4-0.107= | | 78=1/2h(5+8) | | 5.6x+3=4.6x | | 2x-(6x-4)=8-4x | | 10-7x=-(x-12) | | 16x=-50 | | 3y-20=40 | | 8k-2=4 | | Y^2+3y=x^3-x | | 3w-4=4w | | 18(x+3)=2(9x+2)+50 | | 5b-3=-9 | | 4n+15=4n+15 | | 8x+7(-3x-6)=-52-3x | | 10x+18=3(3x+4) | | -12+5x=3(x+2) | | 5-4=u | | 8x-4(40+x)=4 | | 30x-9=21x-53 | | -2n+3+3-7n= | | 3s+12=-6s+6 | | -1.1+u=8 | | 20x-1=4(5x+6) |